The local community perception of tourism development. The case study of Gryfino County – Western Pomerania, Poland - Głąbiński Zbigniew; Duda Tomasz (Bulletin of Geography. Socio-Economic Series)
An increasing number of people from various countries have seen tourism as a chance to develop local economy and quality of life. The article presents the results of the analysis of tourism potential of Gryfino County in Western Pomerania in Poland and confronts them with how it is perceived by the residents. Although the county abounds in great tourist attractions, both of natural and cultural nature and is favourably located in geographic terms, tourism is developing very slowly. In order to examine the reasons for the current situation, an attempt to survey the opinion of the local community on this subject was made by applying the method of Focus Group Interviews. The results emphasise the significance of local community for tourism development in a region.